2003
DOI: 10.1152/ajpheart.00660.2002
|View full text |Cite
|
Sign up to set email alerts
|

High plasma norepinephrine attenuates the dynamic heart rate response to vagal stimulation

Abstract: . High plasma norepinephrine attenuates the dynamic heart rate response to vagal stimulation. Am J Physiol Heart Circ Physiol 284: H2412-H2418, 2003. First published February 21, 2003 10.1152/ajpheart.00660.2002To better understand the pathophysiological significance of high plasma norepinephrine (NE) concentration in regulating heart rate (HR), we examined the interactions between high plasma NE and dynamic vagal control of HR. In anesthetized rabbits with sinoaortic denervation and vagotomy, using a binary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…Buchheit; Laursen and Ahmaidi [6] showed that anaerobic exercise (lactate: 10.9 ± 0.9 mmol.L -1 ) were associated with a low level of parasympathetic modulation reactivation, whereas the moderate intensity exercise (lactate: 3.5 ± 0.2 mmol.L -1 ) induced a more rapid rate of parasympathetic modulation reactivation. Authors like, Kawada et al [20]; Miyamoto et al [27]; Miyamoto et al [28] explain that in the presence of sympathetic activation, vagal stimulation essentially depends on the type and location of the most activated adrenergic receptors. For example, Miyamoto et al [27] showed that the dynamic response of vagal stimulation can be attenuated through activation of postganglionic receptors by high levels of plasma norepinephrine, but not by stimulation of the postganglionic cardiac sympathetic nerve [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buchheit; Laursen and Ahmaidi [6] showed that anaerobic exercise (lactate: 10.9 ± 0.9 mmol.L -1 ) were associated with a low level of parasympathetic modulation reactivation, whereas the moderate intensity exercise (lactate: 3.5 ± 0.2 mmol.L -1 ) induced a more rapid rate of parasympathetic modulation reactivation. Authors like, Kawada et al [20]; Miyamoto et al [27]; Miyamoto et al [28] explain that in the presence of sympathetic activation, vagal stimulation essentially depends on the type and location of the most activated adrenergic receptors. For example, Miyamoto et al [27] showed that the dynamic response of vagal stimulation can be attenuated through activation of postganglionic receptors by high levels of plasma norepinephrine, but not by stimulation of the postganglionic cardiac sympathetic nerve [28].…”
Section: Discussionmentioning
confidence: 99%
“…Authors like, Kawada et al [20]; Miyamoto et al [27]; Miyamoto et al [28] explain that in the presence of sympathetic activation, vagal stimulation essentially depends on the type and location of the most activated adrenergic receptors. For example, Miyamoto et al [27] showed that the dynamic response of vagal stimulation can be attenuated through activation of postganglionic receptors by high levels of plasma norepinephrine, but not by stimulation of the postganglionic cardiac sympathetic nerve [28]. Unfortunately, in this study it was not possible to evaluate the stress of the system (i.e., hormones and muscle metabolites) to verify the level of specific contribution on markers of HRV influencers.…”
Section: Discussionmentioning
confidence: 99%
“…Various investigations have demonstrated complex interactions between the sympathetic and vagal systems with respect to HR regulation (30,32,35,36), resulting in reduced (35) or amplified vagal stimulation (30,32). As recently demonstrated by Sunagawa and coworkers (30,35,36), in the presence of sympathetic activation, HR response to vagal stimulation essentially depends on the type and site of adrenergic receptors most selectively activated under a given condition. For example, Sunagawa et al showed that the dynamic HR response to vagal stimulation can be attenuated via activation of ␣-adrenergic receptors on the preganglionic and/or postganglionic cardiac vagal nerve terminals by high plasma norepinephrine Values are means Ϯ SE.…”
Section: Effect Of Muscular Power Engagement and Anaerobic Process Pamentioning
confidence: 96%
“…levels (35) but not by cardiac postganglionic sympathetic nerve stimulation (36). In contrast, elevated cardiac sympathetic nerve activity can augment the dynamic HR response to vagal nerve stimulation via activation of the postjunctional ␤-adrenergic cascade (30,32).…”
Section: Effect Of Muscular Power Engagement and Anaerobic Process Pamentioning
confidence: 98%
“…The muscle metaboreflex-induced tachycardia occurs primarily via increased sympathetic activity, which may decrease HR gain (19). Indeed, it has been previously shown that high plasma norepinephrine concentration attenuates dynamic HR regulation via the vagus nerve (18), and metaboreflex activation can elicit substantial increases in plasma norepinephrine levels, especially in subjects with heart failure (7).…”
Section: Discussionmentioning
confidence: 99%